2017
DOI: 10.3390/ijerph14090956
|View full text |Cite
|
Sign up to set email alerts
|

Positive Rates and Factors Associated with Abnormal Lung Function of Greenhouse Workers in China: A Cross-Sectional Study

Abstract: Since the number of greenhouse workers are increasing in China, this observational cross-sectional study was designed to evaluate lung function and discuss the potential risk factors, to provide evidence in the surveillance of greenhouse workers’ health. 678 greenhouse workers in Gansu Province, China were enrolled. A questionnaire which included demographic and occupational information was used. Vital capacity (VC), forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and FEV1:FVC ratios (FEV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This study showed that most male farmers were smokers, which confirmed that cigarette was a direct factor of lung dysfunction. 11 Poor use of PPE among farmers was reported in a previous study. The farmers reported feeling uncomfortable in using PPE during handling and spraying pesticide in hot weather.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This study showed that most male farmers were smokers, which confirmed that cigarette was a direct factor of lung dysfunction. 11 Poor use of PPE among farmers was reported in a previous study. The farmers reported feeling uncomfortable in using PPE during handling and spraying pesticide in hot weather.…”
Section: Discussionmentioning
confidence: 77%
“…Occupational lung dysfunction is characterized by chronic cough, sputum, shortness of breath, shortness of breath, chest tightness, chronic bronchitis, asthma, and COPD. 7,11 Furthermore, Indonesia lacks a medical check-up program for farmers to determine the occupational exposure effect of pesticide on lung function.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Spirometry test is widely applied in evaluating patients' respiratory function. FVC, FEV 1 , and FEV 1 /FVC are indicators of obstructive ventilation disorder, [17] usually seen decreased among patients with COPD and bronchial asthma. PEF re ects the function of respiratory muscle and airway resistance while FEF 25-75 acts as an indicator of small airway function.…”
Section: Discussionmentioning
confidence: 99%
“…The spirometer we used to measure lung function was a MasterScreen portable spirometer (Jaeger, Hoechberg, Germany) with a laminar pressure differential flow sensor. The system has a built-in estimated value system, providing a reference standard for lung function of the Chinese population [ 20 ]. The specific standard procedures and methods for spirometry can be seen in Supplemental Materials .…”
Section: Methodsmentioning
confidence: 99%